Ovarian Artery Embolization in a Case of Refractory Obstetric Hemorrhage - Jain,Vikash (Journal of Clinical Imaging Science)
Transcatheteric pelvic artery embolization (PAE) has now become accepted treatment for obstetric hemorrhage providing us the opportunity to control bleeding and avoiding surgical morbidity, preserving uterus, and subsequent fertility. There is little we can offer to the patient if bleeding persists after obstetric hysterectomy and embolization of bilateral uterine and hypogastric arteries. Here in, we present a case of refractory post obstetric hysterectomy hemorrhage where uterine and internal iliac artery embolization failed to control the bleeding. Aortic angiogram showed active contrast extravasation from the ovarian artery, which was successfully embolized with good clinical outcome.